Impact of Right Bank Outfall Drain-I (RBOD-I) / Main Nara Valley Drain (MNVD) on Manchar Lake, Sindh, Pakistan - Mahessar, A. A.; Ansari, K.; Arain, G. M.; Kori, S. M.; Qureshi, S.; Qureshi, A. L. (Engineering, Technology & Applied Science Research, 2019)
The lakes of Sindh are in poor environmental condition due to the massive disposal of effluents. This paper presents the impact of water quality in Manchar Lake due to climate change and anthropogenic intervention. The lake is one of the biggest natural lakes in Sindh, Pakistan. The lake has three major sources of water supply: Indus River, hill torrents from the Khirthar Mountain range and the Right Bank Outfall Drain (RBOD-I)/Main Nara Valley Drain (MNVD). The water supply of the lake from the first two sources has been reduced due to morphological and climate changes. Hence, there is only one, and polluted, water supply to the lake, the RBOD-I/MNVD. At the same time, the use of poisonous materials for fishing has further contaminated the lake’s water. The RBOD system is connected with RBOD-III, RBOD-I/MNVD, Indus Link and RBOD-II on the right side of Indus River for safe disposal of wastewater into the Arabian Sea, which is still not functioning. Hence, more than 4500 cusecs of wastewater from the catchment area of RBOD have directly been discharged into the lake causing severe impact on flora, fauna and the livelihood of locals. In order to analyze the lake water quality impact, the water quality index (WQI) model was used. The results indicate that the water quality of four samples was very poor, while the fifth sample was unsuitable for drinking. The results of statistical analysis of parameters such as TDS, EC, SO4, Cl, Na, and hardness are higher to their permissible limits. Consequently, lake water possesses a high potential risk to local consumers and aquatic ecology.